Two new species of Eleutherodactylus (subgenus Syrrhophus) from western Mexico - Reyes-Velasco, Jacobo; Ahumada-Carrillo, Ivan; Burkhardt, Timothy R.; Devitt, Thomas J. (Zootaxa, 2015)
We describe two new species of Eleutherodactylus, subgenus Syrrhophus, from two separate mountain ranges in western Mexico. Eleutherodactylus grunwaldi sp. nov. inhabits the Sierra de Manantlán in Colima and Jalisco from 1300 to 2200 m, whereas E. wixarika sp. nov. is known from a single locality in the Sierra Huichola of northern Jalisco at 2400 m, but is probably more widespread. Eleutherodactylus grunwaldi is readily distinguishable from most members of mainland Syrrhophus by a combination of its large size, broad, truncate digital pads more than three times the narrowest part of the digit, and a black and green marbled color pattern. This species is saxicolous, inhabiting limestone outcrops, and has been found in caves during the dry season. Eleutherodactylus wixarika is a moderate sized species, most similar to E. teretistes, E. pallidus and E. modestus. It is distinguished from all other members of the subgenus by the combination a tuberculate, reddish dorsum, lack of compact lumbar glands, and expanded digital pads less than twice the width of the narrowest part of the digit. This species inhabits areas with secondary vegetation in pine forest. Males of both species call at night during the rainy season. The advertisement call of both species consists of a short, narrow band, pure-tone note organized into a discrete train at a rate of about six times per minute. Spectral and temporal acoustic properties differ between species. The subgenus Syrrhophus of the genus Eleutherodactylus is one of the most poorly studied groups of frogs in Mexico but probably one of the most diverse.